Evolution in French University Students' Mental Health One Month After the First COVID-19 Related Quarantine: Results From the COSAMe Survey - Wathelet, Marielle; Vincent, Camille; Fovet, Thomas; Notredame, Charles-Edouard; Habran, Enguerrand; Martignène, Niels; Baubet, Thierry; Vaiva, Guillaume; D'Hondt, Fabien (Frontiers in Psychiatry, 2022)
Introduction. The Covid-19 related quarantine had negative psychological effects among university students. Evidence from previous epidemics suggests that negative psychological effects of quarantine measures can last or even worsen after the quarantine lift. The objective of this study was to assess the evolution of students’ mental health and to identify factors associated with mental health outcomes one month after the lift of the lockdown. Materials and methods. This repeated cross-sectional study collected data during the first quarantine in France (T1, N=68,891) and one month after its lift (T2, N=22,540), through an online questionnaire sent to all French university students. Using cross-sectional data, we estimated prevalence rates of suicidal thoughts, severe anxiety (State-Trait Anxiety Inventory, State subscale), depression (Beck Depression Inventory), and stress (Perceived Stress Scale) at T1 and T2. Using longitudinal data (N=6,346), we identified risk factors of poor mental health outcomes among sociodemographic characteristics, precariousness indicators, health-related data, information on the social environment, and media consumption, adjusting for baseline mental health status. Results. We found lower prevalence rates of severe stress (21.7%), anxiety (22.1%), and depression (13·9%) one month after the quarantine compared to the quarantine period (24.8%, 27.5%, and 16.1%, respectively). The prevalence rate of suicidal thoughts increased from 11.4% to 13.2%. Regardless of the existence of symptoms during quarantine, four factors were systematically associated with poor mental health outcomes one month after the quarantine was lifted: female gender, a low feeling of integration before the quarantine period, low quality of social ties during the quarantine, and a history of psychiatric follow-up. Conclusions. The prevalence rates of severe stress, anxiety, and depression, although being lower than during the first lockdown, remained high after its lift. The prevalence rate of suicidal ideation increased. This stresses the need to consider the enduring psychological impact of the pandemic on students as a critical public health issue.